Tailoring the Magnetic and Magneto-Transport Properties of Pd/Co Multilayers and Pseudo-Spin Valve Antidots - Casagrande-Denardin, J (Institute of Physics Publishing, 2018)
Magnetic multilayers and pseudo-spin valves (PSVs) based on Pd/Co were tailored to present well-defined antiparallel magnetization states while maintaining a high perpendicular magnetic anisotropy (PMA). The magneto-electrical properties were measured as a function of intermediate Cu spacers to determine the values that optimize magnetoresistance and the Hall effect. Magnetic multilayers were also deposited on flat porous alumina membranes, forming antidots. The flat antidots shows good PMA and PSVs were studied in these systems for the first time, showing improved magnetoresistance and the extraordinary Hall effect (EHE). Anomalous peaks were obtained in the EHE curves of the PSVs on both continuous films and 40 nm antidots, with four well-defined remnant Hall resistance states. © 2018 IOP Publishing Ltd.